2022
DOI: 10.1113/jp282898
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant movement‐related somatosensory cortical activity mediates the extent of the mobility impairments in persons with cerebral palsy

Abstract: support-information-section).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Having shown that age dependent decreases in hyposensitivity were most prominent for individuals with the greatest functional limitations, we wondered how sensory modality specific changes correlated to related functional areas. For example, prior work suggested aberrant tactile perception drives mobility impairments 26 . Interestingly, tactile hypo-sensitivity had the strongest correlation with age (R 2 = 0.29, Figure 6A) as compared to hyposensitivity related to the vision (R 2 = 0.17, Figure 6B), auditory (R 2 = 0.11, Figure 6C) and proprioception (R 2 = 0.11, Figure 6D) modalities.…”
Section: Individuals With Cp Exhibit Both Hyper and Hypo Sensitivity ...mentioning
confidence: 99%
“…Having shown that age dependent decreases in hyposensitivity were most prominent for individuals with the greatest functional limitations, we wondered how sensory modality specific changes correlated to related functional areas. For example, prior work suggested aberrant tactile perception drives mobility impairments 26 . Interestingly, tactile hypo-sensitivity had the strongest correlation with age (R 2 = 0.29, Figure 6A) as compared to hyposensitivity related to the vision (R 2 = 0.17, Figure 6B), auditory (R 2 = 0.11, Figure 6C) and proprioception (R 2 = 0.11, Figure 6D) modalities.…”
Section: Individuals With Cp Exhibit Both Hyper and Hypo Sensitivity ...mentioning
confidence: 99%